Cardiomyopathies in children with inborn errors of metabolism - I. V. Leontyeva (Rossijskij Vestnik Perinatologii i Pediatrii, 2016)
The paper analyzes the recent literature on cardiomyopathies developing in inborn errors of metabolism. It considers cardiomyopathies as a severe manifestation of primary carnitine deficiency, fatty acid transport and β-oxidation defects, organic acidemias, and lysosomal diseases (including Pompe disease, Danon disease, etc.). Attention is given to diagnostic criteria for the above diseases and to the possibilities of treatment.